2010
DOI: 10.1159/000319497
|View full text |Cite
|
Sign up to set email alerts
|

Association between Clomiphene Citrate and Visual Disturbances with Special Emphasis on Central Retinal Vein Occlusion: A Review

Abstract: <i>Objectives:</i> To determine whether clomiphene citrate (CC) can be implicated as a cause for central retinal vein occlusion (CRVO) and other visual disturbances. <i>Methods: </i>For this systematic review, we performed a search of the following databases: PubMed (1976 to November 2009), Medline Plus 2009, Cochrane Library (1996 to November 2009), Google and Google Scholar (1996 to November 2009). Thirty-five relevant titles (25 full papers and 10 abstracts) were identified and read … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…Thrombophilia associated with exogenous estrogens,6 estrogen progestin oral contraceptives, 7 clomiphene citrate,8 or selective estrogen receptor modulators (SERMS)9 may promote CRVO,8,1014 AF,9,15–17 and CRAO 18–20. Most studies associating estrogen–progestin oral contraceptives with CRVO or CRAO are case reports of only one to three cases 18,2123.…”
Section: Introductionmentioning
confidence: 99%
“…Thrombophilia associated with exogenous estrogens,6 estrogen progestin oral contraceptives, 7 clomiphene citrate,8 or selective estrogen receptor modulators (SERMS)9 may promote CRVO,8,1014 AF,9,15–17 and CRAO 18–20. Most studies associating estrogen–progestin oral contraceptives with CRVO or CRAO are case reports of only one to three cases 18,2123.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, estrogen can directly or indirectly stimulate the visual cortex, thus triggering the development of visual hallucinations. CC causes ocular side effects such as central retinal vein occlusion, irreversible palinopsias, optic neuropathy, anterior uveitis, and maculopathy [610]. Purvin [7] described visual hallucinations in three women treated for infertility with CC for 4 to 15 months.…”
Section: Discussionmentioning
confidence: 99%
“…A computerized PubMed search made by Viola MI et al [5] found only four articles that describe visual problems with Clomifene citrate in fertility patients and were published as case reports. They also found two systematic reviews on the adverse effects of Clomifene and found no visual changes.…”
Section: Discussionmentioning
confidence: 99%
“…Clomifene Citrate has been associated with visual problems, especially with increased dosage or duration of therapy [2]. Visual problems like blurred vision, photophobia, diplopia, scotomata, phosphenes, periphlebitis, central retinal vein occlusion, optic neuropathy and palinopsias has been associated with clomiphene citrate [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%